Bibliometric Analysis of Liveworksheet Utilization in Elementary School - Afifah, Nailatul; Rani, Dewi Eka; Jannah, Raudhotul; Tresnawati, Nailah; Tarmidzi, Tarmidzi (Universitas Negeri Makassar, 2025)
The purpose of this study is to conduct a bibliometric analysis of existing literature, focusing on identifying publication trends, inter-topic connection related to Liveworksheet, the most frequently cited articles, and determining which subjects most widely utilize Liveworksheet in elementary schools. This research employs a bibliometric analysis method using the PRISMA approach. Data were collected through the Publish or Perish application using the Google Scholar database, applying relevant keywords within the time span of 2015–2025. The article selection process involved stages of identification, screening, and eligibility, resulting in 34 articles that were further analyzed. The collected data were extracted in RIS format, stored in Mendeley, and analyzed using the VOSviewer software. The analysis includes network visualization, overlay visualization, and density visualization. The results of the bibliometric analysis indicate a growing trend in the use of Liveworksheet in elementary schools from 2021 to 2024, peaking in 2022 and 2024. Mathematics is the subject that most frequently utilizes Liveworksheet, while other subjects are still limited in their use of this tool in teaching and learning. This study confirms the potential of Liveworksheet in supporting interactive and innovative learning but highlights the need for further research to address limitations and optimize its use across various subjects.